Transbronchial needle aspiration of mediastinal lymph node - How, Soon Hin; Kuan, Yeh Chunn; Ng, Teck Han; Harun, Norra; Kalavathy, Ramachandram; Abdul Rani, Mohammed Fauzi (Malaysian Medical Associations, 2008)
In Malaysia, transbronchial needle aspiration (TBNA) is a relatively new procedure performed only in a handful of respiratory centres. We reviewed TBNA of mediastinal lymph node performed in Hospital Tengku Ampuan Afzan (HTAA) to determine the yield and its complications. Data was retrieved from endoscopy databases and patients' records, CT thorax images and all cytological and histological slides were reviewed. Twenty-five patients had TBNA performed. TBNA was positive in 15 patients (60%). Overall, 80% had confirmed malignancy after bronchoscopy. Only four patients had documented bleeding after TBNA and in two of them, bleeding stopped spontaneously and another two patients required diluted adrenaline to stop the bleed. No mortality was reported from this procedure. Hence, TBNA is a safe procedure.